Genome Sequencing of a Predominant Clonal Lineage of the Grain Aphid Sitobion Avenae - Cubillos-Riffo, F; Villarreal-Diaz, P (Elsevier Ltd, 2022)
The English grain aphid, Sitobion avenae, is a cosmopolitan pest that feeds on cereals, provoking substantial yield losses by injuring plant tissue and by vectoring plant viruses. Here we report a highly complete, de novo draft genome of the grain aphid using long-read sequencing. We generated an assembly of 2740 contigs with a N50 of 450 kb. We compared this draft genome with that of other aphid species, inspecting gene family evolution, genome-wide positive selection, and searched for horizontal gene transfer events. In addition, we described a recent copy number variant expansion of gene families involving aconitase, ABC transporter, and esterase genes that could be associated with resistance to insecticides and plant chemical defenses. This S. avenae genome obtained from a predominant invasive genotype can provide a framework for studying the spatial-temporal success of these clonal lineages in invaded agroecosystems. © 2022 Elsevier Ltd